Surveillance of adverse events following immunization of 13-valent pneumococcal conjugate vaccine among infants, in Zhejiang province, China - Yu Hu; Xuejiao Pan; Fuxing Chen; Ying Wang; Hui Liang; Linzhi Shen; Yaping Chen; Huakun Lv (Taylor & Francis Group, 2022)
Objectives To evaluate the safety of 13-valent pneumococcal conjugate vaccine (PCV13) after its licensure. Methods Review and describe the AEFI reported to national adverse event following immunization surveillance system (NAEFISS) in Zhejiang province from 2017 to 2020. Reporting rates of AEFI were calculated by age, city, severity of AEFI, categories of AEFI, and reaction categories. The data mining algorithm used in this study was reporting odds ratio (ROR). A value of ROR-1.96SE >1 (standard error [SE]) was considered as the positive signal. Results NAEFISS received 3332 AEFI cases following PCV13, with a reporting rate of 17.58/10000 doses. Of the reported AEFI, 652 were serious AEFI cases and the reporting rate was 3.44 for serious AEFI. The reporting rate of fever was the highest among all the clinical diagnosis (7.39/10000 doses). The positive signals were obtained for injection site reaction (ROR-1.96SE: 1.55), hypotonic hyporesponsive episode (HHE) (ROR-1.96SE: 1.62) and febrile seizure (ROR-1.96SE: 1.52). Conclusion The present results supported previous observations that the PCV13 administered as the four-dose schedule was generally well tolerated in Chinese infants as we did not identify any new/unexpected safety concern from the NAEFISS during a four-year time period.